Assessment of causes and control of fire disaster in Arepo neighbourhood, Ogun State, Nigeria. Issue 1 (1st March 2022) - Oloke, O.C.; Oluwatobi, A.O.; Oni, A.; Oke, D.
Abstract: This study examined the occurrence of fire disaster in Arepo community of Obafemi-Owode Local Government Area of Ogun State with emphasis on residential buildings. Questionnaires were administered to 210 adult residents of the neighbourhood while only 150 valid questionnaires are subsequently used for the analysis. Responses were measured on 5-Point Likert scale while the mean score, relative important index as well as frequency and percentages were also used for the analysis. Results were presented with Tables and charts. The study found that residential fire disaster ranked 2 nd among the six segments/object of fire disaster that had occurred in the community. It was further observed that faulty electrical appliances, carelessness and faulty cooking gadget ranked 1 st, 2 nd and 3 rd among the causes of residential fire outbreak in the neighbourhood and that majority of residential housing units are ill-equipped against fire outbreak within the residential neighbourhood in the community. The study therefore concluded by suggesting that government provide firefighting station in the community of Arepo and that the general public has to be enlightened on the importance of providing active firefighting equipment such as fire alarm system, smoke detector, flame detector, heat detector fire extinguisher etc. in their homes.